Tribological properties of stainless steel for artificial hip joints - Hu, Kyle Guotuan. (2011)
The study of tribology on artificial hip joints bearing surfaces has been carried out for many decades. The analysis of the tribological interactions at the bearing surfaces gave researchers many insights as to whether which combination of materials used were suitable for the application. Over the years, the most widely used materials combination for the bearings had been constantly changing with the polymer-on-metal or polymer-on-ceramics being the current leading choice in the market today. However, abrupt failure of artificial hip joints was still commonly reported due to the unpredictable tribological behaviours of the bearing surfaces. Nevertheless, continual studies on tribology have bridged new frontiers in the orthopaedic industry by finding more and more ideal bearing materials. There are still many exciting and unknown possibilities to explore in the world of tribology, especially in joint applications due to the many parameters affecting it. One of these grey areas is the exact effect of wear debris particles on the survivorship of artificial hip joints. In this project, The Author look to identify some of the key trends in specific wear rates and friction coefficient found in earlier reports for metal-on-metal and polymer-on-metal bearing surfaces. He will then design and conduct numerous pin-on-disk experiments to come up with a suitable set of parameters for study and then proceed to determining these trends on stainless steel-on-stainless steel and polymer-on-stainless steel bearing surfaces. All experiments were to be conducted on highly polished stainless steel surfaces. He would also analyze the wear debris particles in terms of its morphology and size, and lastly seek a better understanding of tribo-corrosion in wear experiments. The studies will provide useful information about artificial joints with stainless steel components in it. It will give a better idea of the suitability of stainless steel with the materials that were being tested through the analysis of their friction coefficient and wear rates. The wear debris particle results would also help in understanding the effects it has on the survival of artificial hip joints. Thus, the findings in this project will prove very useful and eligible for future reference in the study of artificial joints and its corresponding wear interactions.